Sentient Lands : Indigeneity, Property, and Political Imagination in Neoliberal Chile - Di Giminiani, Piergiorgio (Book collections on Project MUSE., 2018)
"An ethnographic look at Chile's Mapuche people and how they engage with state-run land restitution efforts via political activism"--Provided by publisher